Mathematical modelling of free convection in a square cavity filled with a bidisperse porous medium for large values of Rayleigh number - REVNIC, Cornelia; PĂTRULESCU, Flavius (Studia Universitatis Babeș-Bolyai Mathematica, 2022)
A free convection problem for bidisperse porous media is considered. The numerical solutions are obtained using an algorithm based on an nonuniform grid. Results for some values of the governing parameters when Rayleigh number is equal to 10⁴ are provided. Mathematics Subject Classification (2010): 76R10, 76S05, 76M20, 65N06. Received 08 September 2020; Accepted 14 December 2020.